2020
DOI: 10.3390/diagnostics10050325
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Morphological Classification of Human Sperm Heads

Abstract: Human infertility is considered as a serious disease of the reproductive system that affects more than 10% of couples across the globe and over 30% of the reported cases are related to men. The crucial step in the assessment of male infertility and subfertility is semen analysis that strongly depends on the sperm head morphology, i.e., the shape and size of the head of a spermatozoon. However, in medical diagnosis, the morphology of the sperm head is determined manually, and heavily depends on the expertise of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…In addition, automatic classification using a gold standard for morphological sperm dataset (SCIAN-MorphoSpermGS; Chang et al, 2017a) and support vector machines (SVMs; Chang et al, 2017b), and a combination of interferometric phase microscopy and SVMs have been reported (Mirsky et al, 2017). Recently, Iqbal et al (2020) established a morphological classification of human sperm heads (MC-HSH) that has higher accuracy than previously reported methods that use the SCIAN or HuSHeM datasets. Unfortunately, most of these analytical methods are based on images captured at ultrahigh magnification (×6300-10,000) using fluorescence microscopy.…”
Section: Future Perspectives For Artsmentioning
confidence: 99%
“…In addition, automatic classification using a gold standard for morphological sperm dataset (SCIAN-MorphoSpermGS; Chang et al, 2017a) and support vector machines (SVMs; Chang et al, 2017b), and a combination of interferometric phase microscopy and SVMs have been reported (Mirsky et al, 2017). Recently, Iqbal et al (2020) established a morphological classification of human sperm heads (MC-HSH) that has higher accuracy than previously reported methods that use the SCIAN or HuSHeM datasets. Unfortunately, most of these analytical methods are based on images captured at ultrahigh magnification (×6300-10,000) using fluorescence microscopy.…”
Section: Future Perspectives For Artsmentioning
confidence: 99%
“…The most visible part of a human sperm image sample is the head of the sperm (Figure 1). This sample is called HSH (Iqbal et al, 2020). A normal HSH image has the head as a point of interest position with a single best guess to detect the head position (Leung et al, 2011).…”
Section: Point Of Interest With Density Estimatormentioning
confidence: 99%
“…Human sperm is unique in shape, which is characterized by the shape of the head, body, and tail. Healthy sperm has a standard head shape, called human sperm heads (HSH) (Iqbal et al, 2020). A method to detect images containing normal HSH based on certain criteria and image processing techniques is needed by medical laboratories (Yoon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In another paper, Ilhan et al [ 25 ] suggested using the Mobile-Net neural network, which has a relatively low number of parameters, for the classification of normal/ab-normal sperms, achieving 87% accuracy. Iqbal et al [ 26 ] developed a custom convolutional neural network (CNN) architecture to categorize human sperm heads, achieving 88% recall on the SCIAN dataset and 95% recall on the HuSHeM dataset. Javadi and Mirroshandel [ 27 ] trained a custom CNN to recognize morphological abnormalities of sperm heads and achieved over 83% accuracy in recognizing acrosome, head, and vacuole defects.…”
Section: Introductionmentioning
confidence: 99%